(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article "The Future of Human Rights: Current Issues in the Study of Challenges and Opportunities" delves into the primary global threats to human rights, including the growth of authoritarian regimes, the effects of climate change, and emerging forms of conflict. It highlights the urgency to reevaluate how these dangers affect human rights and the measures necessary for their protection. Specifically, the article proposes approaches to enhance global collaboration, ensure the consideration of human rights in technological advancements, and support the role of civil society. It advocates for the human rights movement to seize new opportunities to tackle the contemporary challenges faced in the 21st century.